'Berdendang Bergoyang' Effects: Euphoria, Festival Culture, and Event Management Crisis - Meliani Nurul Safitri (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2021)
One sector that has experienced the most decisive impact from the Covid-19 pandemic is organizing events because it involves masses and crowds. Therefore, organizing events attracted attention after the pandemic, including the Dendang Bergoyang Festival held at the Senayan Stadium, Jakarta, in 2022 for three consecutive days. Unfortunately, this event got out of control, causing chaos, and was disbanded by the police. This article analyzes the case of holding the Dendang Bergoyang Festival from the festival culture and event management crisis perspective. Event organizers should have been able to anticipate chaos as a form of community euphoria after being imprisoned by regulations during a pandemic. Understanding festival culture can increase anticipation and prevent crises.